2013
DOI: 10.1177/1049732313494019
|View full text |Cite
|
Sign up to set email alerts
|

Stigma in AIDS Nursing Care in Sub-Saharan Africa and the Caribbean

Abstract: Some nurses who provide AIDS care, in addition to experiencing stigma themselves, also exhibit negative attitudes and perpetrate stigma and discrimination toward persons living with HIV (PLWHAs). We used a participatory research approach to explore the nature, context, and influence of stigma on the nursing care provided to PLWHAs in four low- and middle-income countries: Jamaica, Kenya, South Africa, and Uganda. Eighty-four registered nurses, enrolled nurses, and midwives participated in interviews and 79 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
1
17
0
3
Order By: Relevance
“…When HCWs do not use universal precautions consistently and correctly, they may perpetuate the stigma associated with infectious diseases and act as poor role models for health professions students (Aultman & Borges, 2011). In low-resource countries where HIV stigma is high (Mill et al, 2013;Reda et al, 2009), it is particularly important for nurses to use universal precautions with all patients and with all required procedures. The benefits of practicing universal precautions extend beyond the primary issue of infection control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When HCWs do not use universal precautions consistently and correctly, they may perpetuate the stigma associated with infectious diseases and act as poor role models for health professions students (Aultman & Borges, 2011). In low-resource countries where HIV stigma is high (Mill et al, 2013;Reda et al, 2009), it is particularly important for nurses to use universal precautions with all patients and with all required procedures. The benefits of practicing universal precautions extend beyond the primary issue of infection control.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers (Aultman & Borges, 2011;Mill et al, 2013) have also reported that HCWs made decisions about the practice of universal precautions based on whether the patient looked infectious. A few participants demonstrated some hesitance to care for patients whom they suspected had a communicable disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLWH;Mill, Edwards, Jackson, MacLean, & Chaw-Kant, 2010;Mill et al, 2013). Stigma may result in people at risk for HIV delaying testing (Pottie et al, 2014) and lead to HCP providing differential care to PLWH (Mill et al, 2013).…”
Section: Disclosuresmentioning
confidence: 99%
“…PLWH;Mill, Edwards, Jackson, MacLean, & Chaw-Kant, 2010;Mill et al, 2013). Stigma may result in people at risk for HIV delaying testing (Pottie et al, 2014) and lead to HCP providing differential care to PLWH (Mill et al, 2013). Stigma perpetuated by nurses may be related to a lack of knowledge and educational preparation about HIV clinical management and counseling, religious background, or workplace culture (Waluyo, Culbert, Levy, & Norr, 2015).…”
Section: Disclosuresmentioning
confidence: 99%